EFFECT OF FISHERY CRIMES ON ARTISANAL FISHING COMMUNITIES IN THE COASTAL REGION OF ONDO STATE, NIGERIA - AKINBOYE OA (Innovare Journal of Agricultural Sciences, 2025)
Illegal, unreported, and unregulated fishing activities pose significant threats, undermining local economies and depleting marine resources. This study explores the multifaceted effects of fishery crimes on artisanal fishing communities in the coastal region of Ondo State, Nigeria focusing on the interplay between the socioeconomic characteristics of the fishers and the resultant socioeconomic and environmental effects of such crimes. A multistage sampling technique was used in selecting 150 respondents for the study. Primary data were collected with the aid of a well-structured interview schedule. Descriptive statistical tools used to describe the study’s variables were frequency counts, percentage, mean, and weighted mean score while Pearson product-moment correlation was used to test the study hypothesis. The finding revealed that the mean age of the artisanal fishers was 44 years, while the mean household size was 5 persons, and 11 years was the mean year spent schooling. The mean monthly income was #84,381 while 11 years was the mean years of experience in artisanal fishing. The common socioeconomic effects of fishery crimes on artisanal fishing communities were unemployment and displacement, food insecurity, economic losses, conflict among fishermen, and health impacts while overfishing, by-catch, impact on artisanal practices, depletion of fish stocks and ghost fishing were the common environmental effects. A significant relationship exists between the fishers’ age, household size, years spent schooling, fishing experience, and monthly income and level of effect of fishery crimes on artisanal fishing communities. The study concluded that fishery crimes significantly undermine the sustainability and resilience of artisanal fishing communities with profound socioeconomic and environmental ramifications and recommended engaging artisanal fishing communities in decision-making processes.